Горобина: стан та перспективи культури - Melnichenko, N.V. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2000)
The research deals with up questions of the introduction and selection of the mountain ash species in Ukraine. Their biological characteristics and biological features are given under the conditions of growth in the Forest-Steppe zone of Ukraine. The pomological description and biochemical characteristics of the new cultivars are presented.